2020
DOI: 10.3390/molecules25030618
|View full text |Cite
|
Sign up to set email alerts
|

Human Serum Albumin Aggregation/Fibrillation and its Abilities to Drugs Binding

Abstract: Human serum albumin (HSA) is a protein that transports neutral and acid ligands in the organism. Depending on the environment’s pH conditions, HSA can take one of the five isomeric forms that change its conformation. HSA can form aggregates resembling those in vitro formed from amyloid at physiological pH (neutral and acidic). Not surprisingly, the main goal of the research was aggregation/fibrillation of HSA, the study of the physicochemical properties of formed amyloid fibrils using thioflavin T (ThT) and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
36
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(40 citation statements)
references
References 58 publications
2
36
0
Order By: Relevance
“…This approach was used in the evaluation of the self-assembly of the 33-mer peptide at different concentrations at it is observed in Figure 3 D, E. Here, a red-shift is observed indicating that the tyrosines of the peptide are located in a more hydrophobic environment upon aggregation [ 30 ]. Additionally, this approach was used to evaluate the aggregation upon cation binding of Azurin and RNAse T1 [ 58 ], human serum albumin aggregation into fibrils [ 59 ], gliadin self-organization in aqueous solutions [ 60 ] and the assembly of the Ac-Phe-Phe-Cys-NH 2 (Ac-FFC-NH 2 ) amyloid peptide model [ 61 ].…”
Section: Uv-vis Absorption Spectroscopy and Turbidity Are Initial mentioning
confidence: 99%
“…This approach was used in the evaluation of the self-assembly of the 33-mer peptide at different concentrations at it is observed in Figure 3 D, E. Here, a red-shift is observed indicating that the tyrosines of the peptide are located in a more hydrophobic environment upon aggregation [ 30 ]. Additionally, this approach was used to evaluate the aggregation upon cation binding of Azurin and RNAse T1 [ 58 ], human serum albumin aggregation into fibrils [ 59 ], gliadin self-organization in aqueous solutions [ 60 ] and the assembly of the Ac-Phe-Phe-Cys-NH 2 (Ac-FFC-NH 2 ) amyloid peptide model [ 61 ].…”
Section: Uv-vis Absorption Spectroscopy and Turbidity Are Initial mentioning
confidence: 99%
“…It has been shown that all α-helical proteins show a strong minimum at 222 nm and 208–210 nm and a strong maximum at 191–193 nm. In the case of β-sheet protein, a single negative band may be observed in the 210–225 nm wavelength range and a strong positive band in the 190–200 nm wavelength range, although their intensities are noticeably lower than those for α-proteins [ 66 ]. The CD spectra recorded for buffered solutions of insulin ( 4 ) and hot-spot fragments ( 5 ), ( 6 ) in the presence of HSA as well as for native insulin are presented in Figure 9 a,b.…”
Section: Resultsmentioning
confidence: 99%
“…This allowed for a significant simplification of the procedure and reduced analysis time. The amount of unbound ketoprofen was determined in the supernatant using UV-Vis spectroscopy and the amount of protein-bound ketoprofen was calculated using Equation (1). Because the results obtained for the amount of unbound ketoprofen with free HSA by measuring absorbance and by HPLC were in agreement, for immobilized HSA, the results were based only on measurements of the absorption spectrum.…”
Section: Interaction Of Immobilized Hsa With Kpmentioning
confidence: 99%
“…This makes it one of the most frequently used NSAIDs. It is known that ketoprofen is bounded by the HSA structure at the Sudlow II site (Figure 2b), which, according to literature reports, is very sensitive to oxidizing agents [1]. The properties of KP and its wide application why in the study of the interaction of the drug-HSA it can be used as a model active substance.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation